2018
DOI: 10.1177/0363546518758014
|View full text |Cite
|
Sign up to set email alerts
|

Primary Versus Secondary Osteochondral Autograft Transplantation for the Treatment of Large Osteochondral Lesions of the Talus

Abstract: Clinical outcomes of patients with large OLT treated with secondary OAT after failed marrow stimulation were found to be comparable with those who were treated with primary OAT. These results may be helpful to orthopaedic surgeons deciding appropriate surgical options for patients with large OLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Studies have shown that both mosaicplasty 108 and OATS could fulfill such criteria. 39 Park et al 117 examined whether there is a difference using the OATS as a primary or secondary repair method and could not find any significant difference after a mean follow-up time of 6 years.…”
Section: Osteo(chondral) Transplantationmentioning
confidence: 99%
“…Studies have shown that both mosaicplasty 108 and OATS could fulfill such criteria. 39 Park et al 117 examined whether there is a difference using the OATS as a primary or secondary repair method and could not find any significant difference after a mean follow-up time of 6 years.…”
Section: Osteo(chondral) Transplantationmentioning
confidence: 99%
“…Image enhancement is the most basic technique in image processing technology [4]. Its main purpose is to enhance the useful information in the image, improve the visual effect of the image, according to the characteristics of the original image, purposefully enhance the overall or partial information of the image, and improve the original contrast and sharpness of the image, or the selective enhancement of some interesting details in the image while suppressing the uninteresting part of the image [5]. Meng and Qiao [6] presented a review of different techniques for medical image enhancement to improve the visual appearance of an image and highlighted various image enhancement methods for the medical professional.…”
Section: Introductionmentioning
confidence: 99%
“…For example, patients who received AOT as a second operative treatment had worse outcomes, which may be related to injury to the subchondral bone. 10 In contrast, Park et al 18 presented that patients with large OLT treated with secondary AOT after failed marrow stimulation were found to be comparable with those who were treated with primary AOT. According to the results from our study, both clinical and functional outcomes were improved in patients who received HA injections after failed bone marrow stimulation compared with a pretreatment baseline, and without complications or adverse events.…”
Section: Discussionmentioning
confidence: 96%